Stereotactic radiofrequency ablation as a valid first-line treatment option for hepatocellular adenomas. (31st December 2022) - Laimer, Gregor; Schullian, Peter; Scharll, Yannick; Putzer, Daniel; Eberle, Gernot; Oberhuber, Georg; Bale, Reto
Abstract: Objectives: This study aimed to assess the safety and efficacy of stereotactic radiofrequency ablation (SRFA) in patients with hepatocellular adenomas (HCA). Methods: Retrospective analyses of all patients referred for SRFA treatment at our institution between January 2010 and October 2020 revealed 14 patients (10 women; mean age 34.4 [range, 17–73 years]) with 38 HCAs treated through 18 ablation sessions. Ablations were considered successful if a safety margin >5 mm was achieved. Demographic, interventional, and outcome data were collected and analyzed. Primary and secondary technical efficacy rates were assessed based on follow-up images consisting of contrast-enhanced CT or MR scans. Results: The mean tumor size was 22 mm (range, 7–75 mm). Overall, 37/38 (97.4%) tumors were successfully ablated at the initial SRFA (primary efficacy rate of 97.4%). The median follow-up duration was 49.6 months. No deaths or adenoma-related complications (hemorrhage or malignant transformation) were observed. Disease-free survival rates at 1, 3, and 5 years from the date of the first SRFA were 100%, 85.8%, and 85.8%, respectively. Two patients developed new distant tumors retreated with consecutive re-ablation. No major complications occurred during any of the 18 ablation sessions. Conclusions: Percutaneous thermal ablation is efficient in the treatment of HCAs and may thus be considered a valid first-line treatment option. In addition, SRFA allows for an effective, minimally invasive treatment of large and multiple hepatic tumors within one session.